A Study on Refining the Supply-Demand Balance of "Parks --Residents" in Mountain Community Based --an Example of Yuzhong District, Chongqing, China - Gong, Cong; Cao, Yu; Hu, Changjuan (MAJ - Malaysia Architectural Journal, 2025)
Parks are important public spaces in mountainous communities, serving not only as places for residents to relax and enjoy leisure activities but also as key factors in enhancing community cohesion and promoting sustainable development. How to thoroughly investigate the supply-demand coupling of “park-residents” based on walkability in mountainous communities is an urgent issue to address. This study proposes a “Three-Section” theoretical framework for evaluating “park-residents” supply-demand. It constructs 18 supply indicators for the “Park-City-Residential Area” pathways and 9 demand indicators for residents. Using the CRITIC and coupling coordination model, and based on ArcGIS, the study conducts a quantitative analysis of the supply-demand balance of park-resident interactions in the mountainous communities of Chongqing’s Yuzhong District. It evaluates the rationality of green space layout and the walkability of routes in this area. The results identify communities, parks, and pathways within different coupling coordination ranges and derive the following conclusions: the overall supply level in the study area is relatively high, but there is a significant deficiency in supply in the central and eastern parts; the spatial distribution of supply and demand is relatively imbalanced, showing a basic characteristic of “higher supply in the west and lower in the east, higher demand in the east and lower in the west”; there is a large disparity in local supply-demand matching, with nearly a fourfold difference between the highest and lowest scoring routes. In conclusion, the study’s outcomes offer valuable insights for optimizing the planning and distribution of parks in mountainous communities. By addressing the identified imbalances and disparities, urban planners can improve the accessibility and equitable distribution of green spaces, ultimately promoting greater walkability and ensuring fair access to park resources for all residents.